تأثیر تمرینات تأھیلیة وتقنیة العلاج باللیزر في قوة ومرونة عضلات العمود الفقري للنساء المصابات بالأنزلاق الغضروفي - امال داود عبد الحسن (الرياضة المعاصرة, 2018)
The problem with research in the lack of fitness in women and weak abdominal muscles as a result of repeated births, as well as the weakness of the back muscles, leading to the injury sliding cartilage when performing sudden and strong movement. The importance of research in the use of the latest technology physiotherapy, a laser technology rehabilitative exercises that contribute to the flexibility and power of the spine muscles, and the aim of the research to prepare treatment sessions Laser and exercise rehabilitation to suit the sample and identify the impact of the laser sessions and exercise rehabilitation prepared by the researcher, The hypothesis of the researcht that there are statistically significant differences between before and after the tests in the research variables and in favor of a posteriori tests, the researcher used the experimental approach to design one group testing pre and post consisted research sample (13) of the women with sliding cartilage ages (40-50 years) It was excluded (4) for their involvement exploratory experience, Has also been a homogeneity between them in the research variables, it has concluded the researcher that the laser treatment sessions and exercise rehabilitation stomach helped to improve the strength and flexibility of the back muscles as well as the strength of the abdominal muscles to sample the researcher recommended the necessity of the use of laser therapy and exercise rehabilitation to suit the type of injury, intensity and put the sample. It also recommended a researcher using a laser sessions and rehabilitative exercises stomach and used in the research for the treatment of other different individuals in terms of age and gender .